2014
DOI: 10.1186/s13223-014-0062-9
|View full text |Cite
|
Sign up to set email alerts
|

Successful use of daily intravenous infusion of C1 esterase inhibitor concentrate in the treatment of a hereditary angioedema patient with ascites, hypovolemic shock, sepsis, renal and respiratory failure

Abstract: Hereditary angioedema (HAE) is a rare autosomal dominant disease most commonly associated with defects in C1 esterase inhibitor (C1-INH). HAE manifests as recurrent episodes of edema in various body locations. Atypical symptoms, such as ascites, acute respiratory distress syndrome, and hypovolemic shock, have also been reported. Management of HAE conventionally involves the treatment of acute attacks, as well as short- and long-term prophylaxis. Since attacks can be triggered by several factors, including stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
(27 reference statements)
0
6
0
1
Order By: Relevance
“…The interaction of the two eIF4G proteins with IRES is an essential event for promoting IRES activity. Therefore, viral RNA translation is unaffected [ 48 , 50 ].…”
Section: Cleavage Of Host Proteins Induced By L Promentioning
confidence: 99%
“…The interaction of the two eIF4G proteins with IRES is an essential event for promoting IRES activity. Therefore, viral RNA translation is unaffected [ 48 , 50 ].…”
Section: Cleavage Of Host Proteins Induced By L Promentioning
confidence: 99%
“…3 genetic analysis of C1-INH and other proteins involved in HAE. 59 Pham et al 60 recently reported on successful use of daily intravenous infusion of C1 esterase inhibitor concentrate in the treatment of a patient with HAE and ascites, hypovolemic shock, sepsis, and renal and respiratory failure. Due to the potential severity of attacks, allergists and otolaryngologists must be knowledgeable about the recognition and treatment of laryngeal angioedema.…”
Section: Hae Trauma and Stressmentioning
confidence: 99%
“…Also, C1-INH concentrate is generally well-tolerated in the treatment of CLS after kidney transplantation caused by the preventive treatment of antibody-mediated rejection [ 11 ]. Daily intravenous infusions of C1-INH concentrate also showed effectiveness in patients with HAE accompanied by ascites, hypovolemic shock, and renal and respiratory failure who did not tolerate conventional ICU treatment [ 5 ]. Moreover, C1-INH concentrate is considered a multifunctional regulator of the cascade systems, which were recently shown to improve graft function by inhibiting complement activation and reducing the postoperative inflammation [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, patients are recommended to avoid general anesthesia with endotracheal intubation, or careful prophylactic therapies before surgery are required if surgery with general anesthesia is unavoidable. Besides the well-known clinical presentations, HAE may also produce hypovolemic shock due to the tissue leakage of fluids [ 4 ] and may lead to potentially life-threatening conditions such as capillary leak syndrome (CLS) and disseminated intravascular coagulation (DIC) [ 5 , 6 ]. Here, we report a case of suspected CLS and DIC after kidney transplantation in a patient with HAE.…”
mentioning
confidence: 99%